2019
DOI: 10.18203/2394-6040.ijcmph20191371
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of depression among the elderly living in old age homes and community in Visakhapatnam, India

Abstract: Background: Depression in old age is an emerging public health problem leading to morbidity and disabling effect on the quality of life. Depression in elderly is not yet perceived as a public health problem and is grossly underdiagnosed and undertreated. The physical and social environment plays an important role on the mental health of the elderly. Hence the present study was undertaken to assess and compare the depression among elderly residing in old age homes (OAHs) and community. The objective of the stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…Various study conducted by Ghimire et al, Nagaraj AKM et al, Qadir F et al, Karini D.et al revealed that prevalence of the depression was higher in the old age home than community which was similar to present study. 9,[11][12][13] But in contrast with present study, a study done by George S et al in Ernakulam, Kerala State, India showed no significant difference in both groups. 14 Such difference in findings might be due to the variation in the sociocultural factors, study tools, study population and settings.…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…Various study conducted by Ghimire et al, Nagaraj AKM et al, Qadir F et al, Karini D.et al revealed that prevalence of the depression was higher in the old age home than community which was similar to present study. 9,[11][12][13] But in contrast with present study, a study done by George S et al in Ernakulam, Kerala State, India showed no significant difference in both groups. 14 Such difference in findings might be due to the variation in the sociocultural factors, study tools, study population and settings.…”
Section: Discussioncontrasting
confidence: 86%
“…Score 1 meant that the answer to the question gave one point for depressive symptoms and 0 indicated no point. The symptoms of depression were categorized as normal (0-4), mild (5-8), moderate (9-11) and severe (12)(13)(14)(15). 10 In the present study, score between 0-4 were considered as normal and more than 4 was considered as depressive.…”
Section: Data Collection Toolmentioning
confidence: 90%
“…6,8,9 A study done in Kathmandu valley have revealed depression among elderly living in old-age homes to be nearly double (74.6%) as compared to those living in community (41.8%). 10 The number of elderly living in old-age homes is ever increasing and very less consideration is given about their mental health status. Thus, this study was undertaken to assess depression among elderly living in old-age homes in Devghat, Tanahun, Nepal.…”
Section: Introductionmentioning
confidence: 99%
“…Similar findings were found in a study conducted in Visakhapatnam. 16 Better physical QOL of literate elderly can be attributed to their better understanding of health problems. The better environmental quality of life of retired elderly may be because of their self-satisfaction about physical environment and self-sufficiency in finance.…”
Section: Discussionmentioning
confidence: 99%